Tom Clancy and Orientalism: Political Intrigue and Terrorism In The Jack Ryan Television Series - Alvriza Mohammed Fadly; Jenuri - (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Orientalism describes how the method or way to understand the Eastern world based on geography in the view of Western people, especially the European region. Orientalism explains that the culture and ideology of the Eastern world is believed to be one of the civilizations of the Europeans, judging from its historical heritage such as human civilization, language, and culture. However, this raises a discussion of political issues which are part of the postcolonial discourse, namely the discourse on the identity of the dominant group in the power structure of political representation. This study uses a qualitative method with an analytical descriptive approach and the source of the data obtained is from the Tom Clancy's Jack Ryan series and Tom Clancy's original novel. The results of this study are to describe and analyze the interpretation and depiction of orientalism regarding the East and West through television series shows.